Active thermal management of hotspot under thermal shock based on micro-thermoelectric cooer and bi-objective optimization. (15th January 2022) - Sun, Dongfang; Shen, Limei; Niu, Bingxuan; gao, Cai; Zhou, Pei; Tang, Jingchun; Ye, Bin; Yang, Lei
Highlights: The potential of micro-TEC to mitigate the influence of thermal shock was explored. A lumped reliability enhancement factor of chip was defined. Reliability analysis of chip under thermal shock was carried out. Both the influences of peak temperature and temperature variation were discussed. Operating scheme of micro-TEC to achieve reliability enhancement was investigated. Abstract: The highly non-uniform transient power density in modern semiconductor device leads to thermal shocks with high temperature and temperature variation, which causes performance and reliability challenges. This study established a three-dimensional numerical model to investigate the potential of micro-thermoelectric cooler to mitigate the adverse effect of fluctuating hotspot caused by thermal shock. This study also proposed to assess the chip reliability under thermal shock considering both the influences of peak temperature and temperature variation, and a lumped reliability enhancement factor was defined. Furthermore, the operating scheme of micro-thermoelectric cooler to mitigate the adverse effect of thermal shock was investigated. Results show that the micro-thermoelectric cooler can effectively restrain temperature fluctuation of chip undergoing thermal shock. It also found that keeping the micro-thermoelectric cooler working all the time is not necessarily good considering both the influences of peak temperature and temperature variation. The reliability analysis shows that the lumped reliability enhancement factor is greater than 1 as long as the micro-thermoelectric cooler provides cooling capacity for frequency rising to high. However, for frequency reducing to mild, it is beneficial to turn on the micro-thermoelectric cooler when the ratio of influence weight coefficien is larger than 1, otherwise it is better to turn off the micro-thermoelectric cooler. After the micro-thermoelectric cooler was optimized, the critical ratio of influence weight coefficien could be decreased, indicating a wider practicability of the micro-thermoelectric cooler. Meanwhile, the reliability of chip could be further enhanced. For the case of the ratio of influence weight coefficien equaling to 1, when the thermoelectric element thickness increases from 7.5 μm to 30 μm, the maximum lumped reliability enhancement factor of frequency rising to high and frequency reducing to mild could be respectively improved from 1.9 to 5.4, and 1 to 1.9.